Religious situation in Kazakhstan: analysis of public opinion - Ibrayev, Е.Е.; Zhanpeissova, К.Д. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
Today, the religious situation in Kazakhstan is complicated and constantly developing, as the growing religious awareness of the population, the propaganda activities of foreign religious missions and the peculiarities of national legislation regulating the religious sphere of society lead to various positive and negative consequences. There are several problems associated with the low level of religious literacy of the population, the divergence of value orientations between believers and citizens of the country on an atheistic position, as well as the heterogeneity of ways to spread religious ideas used by different faiths. These questions emphasize the importance of monitoring the religious situation in order to determine the level of religious orientation of the population, the state of relations between representatives of different faiths and religious movements, the level of tolerance and interfaith harmony in Kazakhstan. In this regard, it has been hypothesized that the current religious situation in the country is very complex, its regulation and effectiveness of implementing state bodies is high, empirical research methods studied public opinion, resulting in a positive assessment of the activities of implementing state bodies, proved that the religious situation in the country is stable and favorable. The article contains some results of studying the religious situation in Kazakhstan.